Citizen Response in Crisis: Individual and Collective Efforts to Enhance Community Resilience - Linnell, Mikael (Human Technology, 2014)
This paper reports on the process and findings of an extensive research project with the aim of investigating present initiatives and approaches within the area of community resilience and citizen involvement. The paper specifically addresses which emerging sociotechnical approaches can be discerned within these initiatives. The discussion is structured within three categories of potential voluntary engagement; organized volunteers, semiorganized individuals, and "nonorganized" individuals. The empirical material assembled in the research project is contrasted with contemporary international research literature regarding sociotechnical means for enhancing community resilience. Swedish approaches, as is noted in the Conclusion of the paper, are primarily focused on consuming information in the pre-event phase, rather than on producing information and engaging in collaboration in the response phase.